2019
DOI: 10.1186/s12872-019-1180-6
|View full text |Cite
|
Sign up to set email alerts
|

Body composition is a strong predictor of local carotid stiffness in Swedish, young adults – the cross sectional Lifestyle, biomarkers, and atherosclerosis study

Abstract: Background Obesity has nearly tripled worldwide during the last four decades, especially in young adults, and is of growing concern since it is a risk factor for cardiovascular diseases (CVD). We explored how different body composition measurements are associated with intima media thickness (cIMT) and local stiffness in the common carotid artery, in a subsample of healthy, young women and men, from the Swedish Lifestyle, Biomarkers, and Atherosclerosis (LBA) Study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Previous studies have shown a significant decrease in carotid distensibility associated with BMI, but they calculated distensibility using lumen diameter, not area, leading to a negative association between distensibility and lumen size. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a significant decrease in carotid distensibility associated with BMI, but they calculated distensibility using lumen diameter, not area, leading to a negative association between distensibility and lumen size. 14 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the health-enhancing impact of physical activity on cardiovascular function has been highlighted in healthy young adults aged 18-25 [31]. The findings in [32] also provided evidence for enhanced bioavailable curcumin improving homocysteine and high-density lipoprotein concentrations, which may promote favorable cardiovascular health in young (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) obese men (body mass index ≥ 30.0 kg/m 2 ), in which endothelial function was assessed with the reactive hyperemia index. Furthermore, the endothelial function assessment for vascular relaxation is represented by the quantification of reactive hyperemia (RH) [24], and was validated for type 2 diabetics in [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown body composition measures to be strong predictors of arterial stiffness in young adults [ 17 ] and a regression in arterial stiffness has been seen with weight loss in both obese and nonobese individuals [ 18 ]. Participants for this study were matched for height and weight, so that BMI would not confound blood pressure measures.…”
Section: Discussionmentioning
confidence: 99%
“…The association between aging and blood pressure is complex. It is well known that aging [ 7 9 ] and other factors such as excess food intake [ 18 , 33 ], shift in fat distribution [ 27 ], and lack of exercise [ 14 ], affect vascular hemodynamics but what are less known are factors that decrease this progression. This emphasizes the importance of studies with the goal of continuing to learn about this association and ways to decrease the prevalence of hypertension [ 29 ].…”
Section: Discussionmentioning
confidence: 99%